Pulsed plasma initiated chemical vapor deposition (PiCVD) of polymer layers − A kinetic model for the description of gas phase to surface interactions in pulsed plasma discharges. Issue 12 (21st October 2018) - Loyer, François; Bulou, Simon; Choquet, Patrick; Boscher, Nicolas D.
Abstract : A new kinetic model for studying the growth mechanisms in ultra‐short square pulsed atmospheric‐pressure dielectric barrier discharges (AP‐DBD) is presented. Interpretation of the deposition rates yields information on the dominant mechanisms along each pulse cycle (i.e., initiation, propagation, chain‐transfer, and termination). Further investigations extracted important parameters for the understanding of free‐radical kinetics in the plasma deposition processes. Based on the thin films' chemistry, topography, polymeric length and growth rates, the chemical and physical meaning of the calculated parameters and their impacts on the thin films' polymeric structure are discussed. Abstract : A kinetic model describing the non‐steady plasma‐polymerization mechanisms of pulsed plasma processes using a mixed theoretical‐experimental approach is presented. The behavior of free‐radicals within the reactive volume between the gas phase and the substrate is investigated, highlighting key mechanisms in the growth of polymers and plasma‐polymers together with the necessity of temporally isolating the discharge to promote conventional polymerization pathways.